Digitizing Tax Collection as a Mechanism to Ensure Tax Revenues - A Study of the Experiences of Egypt and Jordan - boumad, soumia; djennai, mohamed alaaeldinne (Journal of Research in Finance and Accounting, 2023)
This research paper aims to highlight the role of digitizing tax collection in ensuring tax revenues and shed light on the significant economic gains achieved through this digitization process. This is achieved by transitioning from the traditional form of tax payment to the electronic form, which in turn guarantees transparency and more credible and simplified procedures. The paper also presents the experiences of both Egypt and Jordan in this field, along with demonstrating the main challenges and difficulties encountered during the digitization process. The research paper found several key results, including that digitizing tax collection enhances tax transparency and spreads tax awareness concerning electronic tax payment and various tax transactions, such as submitting electronic tax returns. It also leads to an increase in tax compliance levels. Both Egypt and Jordan witnessed a noticeable development in the proportion of electronically collected tax revenues in relation to the total tax revenues. Furthermore, they were able to gather accurate and comprehensive information through the electronic submission of tax returns. Governments were able to achieve stakeholder satisfaction by saving time and effort and providing continuous service around the clock for twenty-four hours.